Elaboration of questions with multiple choices using the liveworksheets.com platform - Messias, Júlio Brando; Messias, Inalda Maria de Oliveira; Araújo , Rosane Jamille de Oliveira; Florêncio, Mônica Simões; Filho, João Ferreira da Silva; Luz , Betty Rose de Araújo; Silva, Silvana de Fatima Ferreira da (Seven Editora, 2023)
With the COVID-19 pandemic, educational institutions around the world have had to adapt, and emergency remote learning has been the solution found to continue the school year. The pandemic has made it difficult to conduct in-person assessments, which has enabled teachers to adopt online alternatives for creating educational activities and among them exams. Liveworksheets.com is a platform that makes it possible to transform traditional printable tasks (pdf, jpg, png) into interactive exercises with self-correction, called "interactive spreadsheets". The objective of this work is to present the versatilities of an educational platform, little known in the national academic environment, but which has a pedagogical potential that allows successful results for the dynamics of the classroom. The article addresses the different possibilities of the interactive tool, specifically directed to the elaboration of questions of multiple alternatives, being an exploratory research of bibliographical character. The platform allows you to elaborate questions of multiple choices of five different modalities: (1) of "marking with X"; (2) "right or wrong"; (3) "select yes or no"; (4) "check box dropped" and (5) "true or false". In the end it was possible to see how dynamic the platform is being a tool that makes the most of educational technologies. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-173